THE BOZOK SETTLEMENT IN THE SYSTEM OF CULT OBJECTS OF THE STEPPE EURASIA (Journal of history, 2019)
In the article we describe the history of the research of the memorial complexes of the steppe Eurasia. The most striking are the ancient Turkic memorial temples of Central Asia and Southern Siberia (Kultegin, Bilge-kagan, Bugut, Saryg-Bulun). Among these architectural objects are the monumental square forms of «hillforts», explored in the western part of the Eurasian steppe (Glodosy, Voznesenka, Pereshchepino). In their design are recorded details known from written evidence: quadrangular shape, wall-shaft, moat, traces of pillars from internal structures, specially designed entrance, single artifacts left from the offerings. However, there are no traces of permanent habitation in the form of dwellings, fireplaces, household pits. The first excavations of «square hillforts», carried out in the 30s of the XX century, caused difficulties in interpreting of their functional purpose and dating. Like everything mysterious in archeology they were categorized as cult memorials of the early Middle Ages. At present, we can assert that these complexes as places of ritual ceremonies and rites have been confirmed in the materials of the Bozok archaeological microdistrict.